"Bridging the Gap" international ECLS training and simulation - evaluation of the 10th educational corner on EuroELSO congress 2022 in London, United Kingdom. (May 2023) - Cvetkovic, Mirjana; Antonini, Marta V; Rosenberg, Alex; Meadows, Christopher IS; Dąbrowski, Marek; Puslecki, Mateusz; Fawzy Hassan, Ibrahim; Fowles, Jo-Anne; O'Callaghan, Maura; Stefaniak, Sebastian; Riera, Jordi; Barrett, Nicholas A; et al.
Introduction : Simulation training offers an authentic team-based learning opportunity without risk to real patients. The Educational Corner at the annual congress of the European Branch of Extracorporeal Life Support Organisation (EuroELSO) provided an opportunity for multiple simulation training sessions facilitated by experts from all over the world. Aim : We aimed to review the educational impact of EuroELSO Educational Corner and whether it provides a quality ECLS training to a wide spectrum of multidisciplinary international attendees utilising high and low fidelity simulation, workshops and hands on sessions. Methods : During the congress, 43 sessions were conducted dedicated to ECLS education with identified educational objectives. The sessions focused on management of adults and children on V-V or V-A ECMO. Adult sessions covered emergencies on mechanical circulatory support with management of LVAD and Impella, managing refractory hypoxemia on V-V ECMO, emergencies on ECMO, renal replacement therapy on ECMO, V-V ECMO, ECPR cannulation and performing perfect simulation. Paediatric sessions covered ECPR neck and central cannulation, renal replacement on ECMO, troubleshooting, cannulation workshop, V-V recirculation, ECMO for single ventricle, PIMS-TS and CDH, ECMO transport and neurological injury. Results : The Educational Corner was attended by more than 400 participants over the two congress days. Majority of responders (88%) reported that training sessions met the set educational goals and objectives and that this would change their current practice. Almost all (94%) reported that they received useful information and 95% would recommend the session to their colleagues. Conclusion : The Educational Corner, as an integral component of the annual EuroELSO congress, achieved the set educational goals and provided quality education based on the recipient survey. Structured multidisciplinary ECLS education with standardised curriculum and feedback is an important key step in delivering quality training to an international audience. Standardisation of European ECLS education remains an important focus of the EuroELSO.